A renormalization scheme and skewness of height fluctuations in (1 + 1)-dimensional VLDS dynamics. (25th February 2016) - Singha, Tapas; Nandy, Malay K
Abstract: We study the (1 + 1)-dimensional Villain, Lai, and Das Sarma (VLDS) equation driven by a Gaussian white noise and implement a renormalization scheme without rescaling at one-loop order. Using a diagrammatic method, we calculate the renormalized second and third moments in the large-scale and long-time limits. The ensuing skewness value is S = −0.0441. This (negative) value is consistent with the numerical prediction of Das Sarma et al (1996 Phys. Rev . E 53 359 ).